Pengabdian Guru dalam Mengimplementasikan Metode Al-Asas di Pondok Pesantren Al-Mubarok Lanbulan Sampang Madura - Febrianto; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Yellow books are Islamic books in Arabic or other languages ​​that serve as references for Islamic scholarly traditions in Islamic boarding schools, but to understand them requires an understanding of Arabic grammar. The Al-Asaas method is a learning strategy designed to facilitate students, especially new students, in understanding Arabic language rules and improving their reading skills in yellow books that do not contain vowels. Al-Mubarok Lanbulan Islamic Boarding School is one of the Islamic educational institutions that created this method and has implemented this approach. The Al-Asaas method can help new students of Al-Mubarok Lanbulan Islamic Boarding School to understand the rules of nahwu more easily. This research uses descriptive qualitative with case studies. To reach the expected conclusion, an appropriate strategy is needed to improve the understanding of Arabic grammar and technical preparation is needed in the learning process. For example, teachers must be given guidance before the teaching and learning process. Students are given tests and guidance in learning Arabic pegon writing beforehand. In its implementation, Al-Asas uses a 5-volume module system. Students are required to memorize the basic principles of Al-Asas. Implementation results show that students are able to read the book in a short time without vowels and meanings, along with its structure and basis. Therefore, the Al-Mubarok Lanbulan Islamic Boarding School created and chose the Al-Asas method as a quick way to read the book.